Palenque de San Basilio in Colombia: Genetic data support an oral history of a paternal ancestry in Congo (2016)
The Palenque, a black community in rural Colombia, have an oral history of fugitive African slaves founding a free village near Cartagena in the seventeenth century. Recently, linguists have identified some 200 words in regular use that originate in a Kikongo language, with Yombe, mainly spoken in the Congo region, being the most likely source. The non-recombining portion of the Y chromosome (NRY) and mitochondrial DNAwere analysed to establish whether there was greater similarity between present-day members of the Palenque and Yombe than between the Palenque and 42 other African groups (for all individuals, n = 2799) from which forced slaves might have been taken. NRY data are consistent with the linguistic evidence that Yombe is the most likely group from which the original male settlers of Palenque came. Mitochondrial DNA data suggested substantial maternal sub-Saharan African ancestry and a strong founder effect but did not associate Palenque with any particular African group. In addition, based on cultural data including inhabitants’ claims of linguistic differences, it has been hypothesized that the two districts of the village (Abajo and Arriba) have different origins, with Arriba founded by men originating in Congo and Abajo by those born in Colombia. Although significant genetic structuring distinguished the two from each other, no supporting evidence for this hypothesis was found. © 2016 The Author(s) Published by the Royal Society. All rights reserved.